Dramatis Personae and narrative instance - Vescovo, Piermario (Status Quaestionis, 2022)
Going beyond the opposition between two models, the so-called dramatic text and the so-called narrative text (intended also in the semiotic meaning of the term), this essay will try to refer to two connected and interactive instances and raise, according to a principle that follows a semantic and not a semiotic articulation, the question of the interweaving of the dramatic and the narrative. Relevant examples of this are visible in the entire history of Western theatre, but in a current of the recent experimentation linked to the theatrical use of the novel, especially in the absence of a return to the consuetudinary dramaturgical canons and in the direct incorporation of the scene.